Early commissioning results for spectroscopic X‐ray Nano‐Imaging Beamline BL 7C sXNI at PLS‐II. (18th October 2017) - Lee, Sangsul; Kwon, Ik hwan; Kim, Jae-Young; Yang, Sung-Sun; Kang, Sechang; Lim, Jun
Abstract : The details and capabilities of a newly upgraded imaging beamline, 7C sXNI, are described for both high‐resolution tomography and spectroscopic imaging. Abstract : For spectral imaging of chemical distributions using X‐ray absorption near‐edge structure (XANES) spectra, a modified double‐crystal monochromator, a focusing plane mirrors system and a newly developed fluorescence‐type X‐ray beam‐position monitoring and feedback system have been implemented. This major hardware upgrade provides a sufficiently stable X‐ray source during energy scanning of more than hundreds of eV for acquisition of reliable XANES spectra in two‐dimensional and three‐dimensional images. In recent pilot studies discussed in this paper, heavy‐metal uptake by plant roots in vivo and iron's phase distribution in the lithium–iron–phosphate cathode of a lithium‐ion battery have been imaged. Also, the spatial resolution of computed tomography has been improved from 70 nm to 55 nm by means of run‐out correction and application of a reconstruction algorithm.